Service quality dimensions manifest in Omnichannel supermarket retail - Falatouri, Taha; Chromjaková, Felicita (Serbian Journal of Management, 2024)
Businesses have increasingly adopted omnichannel retail strategies to deliver seamless services and enhance customer experiences across multiple channels. However, many have done so without fully understanding customer expectations in the globally integrated market. Despite the rise of new customer expectations compared to traditional services, research on service quality within omnichannel retail remains scarce. This study aims to fill that gap by examining how service quality dimensions manifest in omnichannel supermarket stores. Using a text mining approach, we analyzed 7,216 online customer reviews of omnichannel supermarkets. The findings reveal that while traditional dimensions such as personal interaction, efficiency, and fulfillment remain valuable to customers, new critical dimensions such as integration and compensation have emerged in omnichannel retail. Additionally, the results show that customer expectations have evolved, prioritizing factors beyond price in omnichannel services. Reliability of contact and system availability are essential, while product shortages are identified as the most dissatisfying aspect.
Keywords: omnichannel retail; text mining; service quality; supermarket chain